Optimizing the protocol for vitrification of individual spermatozoa by adjusting equilibration time. (3rd May 2020) - Belenky, Michael; Itzhakov, Diana; Freger, Vita; Roseman, Orna; Abehsera, Sarah; Miller, Netanella; Berkovitz, Arie
ABSTRACT: Efficient cryopreservation of small numbers of human spermatozoa is essential in cases of severe male infertility, especially those requiring surgical sperm retrieval. Although vitrifying individual spermatozoa on sperm vitrification devices (SpermVD®) provided optimal cell retrieval upon warming, motility rates tended to be lower than with bulk-freezing. Post-warming motility is directly affected by cryoprotectant exposure; however, optimal cryoprotectant equilibration time is unknown. We evaluated several timeframes exposing individual spermatozoa to cryoprotectant before freezing and different cryoprotectants. A total of 2, 925 spermatozoa from 20 patients ranging from normozoospermic to moderate oligoteratoasthenozoospermic were vitrified in small groups, on 60 SpermVD®, in 1 µl droplets of 1:1 v/v cryoprotectant/washing medium mixture. Each group was vitrified after 2–60 minutes equilibration time. Motility of each group was evaluated after warming. Leftover pellets were frozen in cryotubes in a mixture of 1:1 v/v cryoprotectant/washing medium after 10 minutes equilibration at room temperature and 10 minutes on liquid nitrogen vapors. Post-thaw motility correlated negatively with cryoprotectant exposure time. The highest post-warming motility rate (32.1%) was observed with 8-minutes equilibration. After 10 minutes, motility rate of vitrified sperm was lower than that of bulk-freezing (31.7% vs. 37.0%, p < 0.0001). Different cryoprotectants did not affect the results. Therefore, for vitrifying small numbers of spermatozoa, we suggest maximum equilibration time of 8-minutes to achieve maximum motility after warming.